Frames of Racism in Novel “Dear Martin” by Nic Stone 2017 - Muh. Anshar Wadi; Faidah Yusuf; Waode Surya Darmadali (LETS: Journal of Linguistics and English Teaching Studies, 2022)
The aim of the research is to know how the central frames of color-blind racism are experienced by minorities in Nic Stone’s novel Dear Martin. This research used a descriptive qualitative method. In collecting the data, the researcher analyzed the object by using the theory of color-blind racism by Bonilla Silva. The results of the research are in the form of several findings about racist acts in ideology of color-blind racism by the majority (white people) against the minority (black people) especially the teenager of African-American. There are four central frames of color-blind racism as the problem of this research, namely; Abstract Liberalism, Naturalization Racism, Cultural Racism, and Minimization Racism. The researcher found that racist acts still occur in African-American life based on the four central frames color-blind racism system applied to racial equality in the novel.